Kegiatan Lesson Study Model Pembelajaran Seni Budaya Kelas VII MTs NW Mengkuru - Junaidi, Junaidi; Maimanah, Hasbul; Inayah, Nurul; Aini, Wahidatul; Hirsan, Muh (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2025)
Lesson Study is a lecturer activity by doing preparation (plan), implementation (do), reflection and (see)). Plan using a student-centered learning approach is expected to enable students to participate actively. Do is done by implementing learning process-oriented approach to students (student centre learning). The learning model consists of contextual instruction method, small group discussion, cooperative learning, project base learning or simulation, discovery learning, collaborative learning, self-directed learning, and problem base learning. See is done in the form of discussion that starts from the delivery of the teacher impression that has been practicing the learning by giving comments or general impression as well as the special impression on the learning process. All observer teacher deliver responses or suggestions wisely to the learning process that has been implemented and responses are delivered with the support of the evidence obtained.Various findings and valuable inputs delivered during the discussion in this stage of follow-up can be a capital for teacher when teaching or becoming an observer lecturer to develop a better learning process.